Wychowawcza rola orkiestr szkolnych w gimnazjach autonomicznej Galicji - Juśko, Edmund; Niedojadło, Andrzej (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
Orchestras existed in most high schools. They were composed of either wind or string instruments but rarely were they mixed. Sometimes interest circles of music lovers or mandolin players cooperated with the orchestras. In general, the activity of the orchestras developed successfully. The students were actively interested in music and developed their skills in the orchestra. In most cases, they were hampered by financial issues related to the cost of purchasing and maintaining their instruments. The orchestras were supervised by teachers, professors, and sometimes professional musicians who had enthusiasm for this kind of work, but often worked for small fees. The orchestras mostly performed during school celebrations. In practically all the junior high schools, they performed separate soirées in honor of each of the Three Bards (Adam Mickiewicz, Juliusz Słowacki, and Zygmunt Krasiński). Other celebratory performances included the following themes: the anniversaries of the November and January Uprisings, the May 3rd Constitution, anniversaries of the reign of the Habsburg dynasty, anniversaries of the death or birthday of Maria Konopnicka, Piotr Skarga, Reverand Jozef Poniatowski, and the anniversaries of Polish victories at Vienna, or Grunwald, and other events important to national history. School orchestras also played in student marches and parades, during games, excursions, and religious events. Additionally, they often played during events for the wider public by participating in official ceremonies, festivals, and picnics. For this reason, they garnered public sympathy and social support which was very important, especially when buying instruments. The orchestras had a powerful influence on the students’ interests in music because being part of the orchestras taught them sensitivity to aesthetics and beauty. Their participation in the ceremonies related to the cultivation of national traditions and customs contributed to the formation of patriotic feelings among the students.